Game-play affects hamstring but not adductor muscle fibre mechanics in elite U20 basketball athletes - Akundov, R.; Saxby, D. J.; Diamond, L. E.; Snodgrass, S.; Clausen, P.; Drew, M. (Sports Biomechanics, 2025)
Muscle tendon unit fibre mechanics of hamstring and adductor strain injuries are not well studied, with factors such as fatigue promoted as risk factors in the absence of mechanistic evidence. In this study, musculoskeletal modelling was used to estimate fibre mechanics of four hamstring (biceps femoris long head, biceps femoris short head, semimembranosus and semitendinosus) and four adductor (adductor brevis, adductor longus, adductor magnus and gracilis) muscles during an anticipated cut task. The cut task was performed by 10 healthy elite male U20 basketball players both before and immediately after they played in one (of four) competitive basketball game. Biceps femoris long head produced significantly lower (p = 0.032) submaximal force post-game in the latter part of swing (30.7% to 35.0% of stride), though its peak force occurred later (37%) and remained unchanged. Semimembranosus produced significantly lower (p = 0.006) force post-game (32.9% to 44.9% of stride), which encompassed the instance of peak force (39%). Neither fibre velocity nor fibre length of the investigated muscles were significantly affected by game-play. These finding suggest that if fatigue is a factor in hamstring and adductor muscle strain injuries and is brought about by game-play, it is unlikely through the fibre mechanisms investigated in this study.